Autophagy-dependent release of zinc ions is critical for acute lung injury triggered by zinc oxide nanoparticles. Issue 9 (21st October 2018) - Jiang, Xuejun; Tang, Qianghu; Zhang, Jun; Wang, Hong; Bai, Lulu; Meng, Pan; Qin, Xia; Xu, Ge; Bose, Diptiman D.; Wang, Bin; Chen, Chengzhi; Zou, Zhen
Abstract: Pulmonary exposure to zinc oxide nanoparticles (ZnONPs) could cause acute lung injury (ALI), but the underlying molecular mechanism remains unclear. Herein, we established a ZnONPs-induced ALI mouse model, characterized by the histopathological changes (edema and infiltration of inflammatory cells in lung tissues), and the elevation of total protein and cytokine interleukin-6 in bronchoalveolar lavage fluid in time- and dose-dependent manners. This model also exhibited features like the disturbance of redox-state (reduced of glutathione to glutathione disulfide ratio, elevation of heme oxygenase-1 and superoxide dismutase 2), the decrease of adenosine triphosphate synthesis and the release of zinc ions in the lung tissues. Interestingly, we found that ZnONPs exposure caused the accumulation of autophagic vacuoles and the elevation of microtubule-associated proteins 1A/1B light chain (LC)3B-II and p62, indicating the impairment of autophagic flux. Our data indicated that the above process might be regulated by the activation of AMP-activated protein kinase but not the mammalian target of rapamycin pathway. The association between ZnONPs-induced ALI and autophagy was further verified by a classical autophagy inhibitor, 3-methyladenine (3-MA). 3-MA administration reduced the accumulation of autophagic vacuoles, the expression of LC3B-II and p62, followed by a significant attenuation of histopathological changes, inflammation, and oxidative stress. More importantly, 3-MA could directly decrease the release of zinc ions in lung tissues. Taken together, our study provides the evidence that ZnONPs-induced pulmonary toxicity is autophagy-dependent, suggests that limiting the release of zinc ions by inhibiting autophagy could be a feasible strategy for the prevention of ZnONPs-associated pulmonary toxicity.